A modified QuEChERS method coupled with high resolution LC-Q-TOF-mass spectrometry for the extraction, identification and quantification of isoflavones in soybeans. Issue 10 (23rd February 2016) - Ding, Bo; Wang, Zhiyuan; Yi, Rong; Zhang, Siqun; Li, Xun; She, Zhigang; Chen, Wenrui
Abstract : A modified QuEChERS method coupled with high resolution LC-Q-TOF-MS was established for the extraction, identification and quantification of six isoflavones in soybeans. Abstract : A modified QuEChERS method coupled with high resolution LC-Q-TOF-MS was established for the extraction, identification and quantification of six isoflavones including daidzein, glycitein, genistein, daidzin, glycitin and genistin in soybeans. Individual isoflavones were identified on the basis of the accurate mass data of their protonated mass ions, isotope ion patterns, and fragment ions respectively. The extraction conditions of isoflavones, including the soybean content, concentration of MgSO4 and NaCl, ACN : H2 O ratio and ultrasonic time, were optimized by applying the orthogonal experiment and response surface methodology designs. The established QuEChERS pretreatment method combined with LC-Q-TOF-MS was an effective analytical method for the simultaneous characterization and quantification of isoflavones with high selectivity, high linearity ( r 2 > 0.998) in a wide range, low LOD and LOQ, and high precision. The method was successfully applied to determine isoflavones in genetically modified (GM) and non-genetically modified soybeans. And it was found that the concentrations of daidzin, genistin and glycitin in GM soybeans were higher than in non-GM soybeans.